Evaluation and Projection of Airport Landing Movement Areas based on Statistical Analyses, ICAO 2013 Manuals and KM 44, 2002 Regulation - Ari Sandhyavitri; Fiqri Fansyuri (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2020)
This article demonstrated how to calculate an airport landing movement in systematic five main stages encompassing; (i) data collection (including passengers data, aircraft movements, population, GDP, per capita income, cargos movement, temperatures, ground elevation, slope surface, wind speed, and aircraft characteristics), (ii) forecasting the future traffic demands, (iii) calculating aerodrome reference field length (ARFL), (iv) define aerodrome reference code (ARF), and (v) calculate runway dimensions, taxiways, and apron areas. This article has selected Hang Nadim International Airport (HIA) as a case study. It was identified that the aircraft movements in this airport have increased by an average of 7.30% every year in the periods of 2007 to 2016. This Airport has an existing apron with a capacity of 13 aircraft, while the apron currently has to accommodate 19 aircraft. Therefore, to anticipate future demand. This research evaluated and forecasted the requirements standard for the airport landing movement areas in 2026. Based on the International Civil Aviation Organization (ICAO) 2013 manuals and KM 44, 2002 regulation concerning the National Airport Regulation. This article recommended that the existing runway and taxiways would be adequate to facilitate future aircraft movements up to 2026. However, the apron requires to be expanded to 1,600 m x 150 m (which a capacity of 31 aircraft) for accommodating the apron requirements standard in 2026.